Primary Ewing Sarcoma of Kidney in an Adult: An Oddball - Mahajan, Nidhi; Mahanta, Neelakshi; Ray, Arpita; Phukan, Mandakinee; Saini, Naveen (Indian Journal of Case Reports, 2024)
Ewing sarcoma (ES) is a malignant bone and soft-tissue tumor derived from neuroectoderm. It occurs, mostly, in pediatric adolescentswith the histopathological features of invasiveness. The occurrence of ES of the kidney is rare, comprising only 1% of all renal tumorswhich are limited to case reports and small case series. Herein, we report a case of a 44-year-old male patient, presenting with the rightflank pain and hematuria. Computed tomography scan demonstrated a right midpolar exophytic renal mass with intraluminal right renalvein and inferior vena cava (IVC) thrombus without visceral metastasis suggesting the diagnosis of renal cell carcinoma (T3BN0M0).The patient underwent the right radical nephrectomy with IVC thrombectomy. In view of the aggressiveness of the tumor, the patientreceived adjuvant chemotherapy (i.e., four cycles of vincristine, adriamycin, and cyclophosphamide alternating every 3 weeks with fourcycles of ifosphamide and etoposide). The patient had near-complete resolution of the tumor with no thrombus seen in the follow-upscan. We could not complete six cycles of chemotherapy which were planned initially due to recurrent cytopenias. Six months postchemotherapy,the patient is clinically and radiologically disease-free and is in close follow-up. We are reporting this case to highlightthe rarity of this entity and its challenging clinicopathological diagnosis when presenting as a renal tumor.